EFFECT OF MANAGEMENT CONTROL SYSTEM AND INTERNAL CONTROL ON COMPANY PERFORMANCE AT PT. GLOBAL JET EXPRESS SURABAYA - Apriliasari, Ria Dini (International Journal of Global Accounting, Management, Education, and Entrepreneurship, 2021)
This study aims determine to the effect of the control system on company's performance at PT Global Jet Express Surabaya and the influence internal control on the performance of the Global Jet Express Surabaya company and the influence of the management control system and internal control on the company's performance at PT Global Jet Express Surabaya. This study is a kind of descriptive study, and there is a quantitative study. PT. Global Jet Express South Surabaya has approximately 155 employees. A sample of this study was an employee of Global Jet Express, an office in southern Surabaya. NS. A total of 35 people in the accounting department, staff working in the budget area, and the department. In this study, we used a targeted sampling technique, that is, a method of determining samples from a specific point of view. Data collection method by questionnaire. The data analysis method in this study uses multiple linear regression analysis. Based on the results data analysis, we can conclude that there is a significant positive impact between the control systems on the performance of PT Global Jet Express Surabaya. There is a positive and significant impact between the internal control over Global Jet Express Surabaya's performance and the joint positive and significant impact between the management control system and internal control over PT Global Jet Express Surabaya's performance.